Peran Orientasi Pasar, Program Promosi dan Inovasi dalam Menentukan Kinerja Pemasaran Jasa - Retno Dewanti; Henderi Budi Utomo; Andrie Hidayat (Bina Nusantara University, 2010)
Experience, hard work, and support from the management team and skilled staff have made WOM Finance to be one of the best consumer’s financing companies in Indonesia. Therefore, it is important to do an evaluation on the performance of marketing. The method of analysis with the help of statistical regression correlation showed that market orientation significantly has partial influence on improving credit services marketing performance. Promotion program is also has significant partial effect on marketing performance, as well as economic innovation that has successfully influenced marketing performance. However, when market orientation is conducted jointly with the program of economic promotion and innovation it did not bring a positive impact so that in the present moment the emphasis needs to be evaluated on choice of orientation activities.